Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №791

Разложите на множители многочлен:
а)
$a^3 - 2a^2 + 2a - 4$
;
б)
$x^3 - 12 + 6x^2 - 2x$
;
в)
$c^4 - 2c^2 + c^3 - 2c$
;
г)
$-y^6 - y^5 + y^4 + y^3$
;
д)
$a^2b - b^2c + a^2c - bc^2$
;
е)
$2x^3 + xy^2 - 2x^2y - y^3$
;
ж)
$16ab^2 - 10c^3 + 32ac^2 - 5b^2c$
;
з)
$6a^3 - 21a^b + 2ab^2 - 7b^3$
.

Решение а

$a^3 - 2a^2 + 2a - 4 = (a^3 - 2a^2) + (2a - 4) = a^2(a - 2) + 2(a - 2) = (a - 2)(a^2 + 2)$

Решение б

$x^3 - 12 + 6x^2 - 2x = (x^3 - 2x) + (6x^2 - 12) = x(x^2 - 2) + 6(x^2 - 2) = (x^2 - 2)(x + 6)$

Решение в

$c^4 - 2c^2 + c^3 - 2c = (c^4 - 2c^2) + (c^3 - 2c) = c^2(c^2 - 2) + c(c^2 - 2) = (c^2 - 2)(c^2 + c) = c(c^2 - 2)(c + 1)$

Решение г

$-y^6 - y^5 + y^4 + y^3 = (y^4 - y^6) + (y^3 - y^5) = y^4(1 - y^2) + y^3(1 - y^2) = (1 - y^2)(y^4 + y^3) = y^3(1 - y^2)(y + 1)$

Решение д

$a^2b - b^2c + a^2c - bc^2 = (a^2b - b^2c) + (a^2c - bc^2) = b(a^2 - bc) + c(a^2 - bc) = (a^2 - bc)(b + c)$

Решение е

$2x^3 + xy^2 - 2x^2y - y^3 = (2x^3 + xy^2) - (2x^2y + y^3) = x(2x^2 + y^2)(x - y)$

Решение ж

$16ab^2 - 10c^3 + 32ac^2 - 5b^2c = (2x^3 + xy^2) - (2x^2y + y^3) = x(2x^2 + y^2) - y(2x^2 + y^2) = (2x^2 + y^2)(x - y)$

Решение з

$6a^3 - 21a^b + 2ab^2 - 7b^3 = (2ab^2 + 6a^3) - (7b^3 + 21a^2b) = 2a(b^2 + 3a^2) - 7b(b^2 + 3a^2) = (b^2 + 3a^2)(2a - 7b)$